Estudo da remoção de dióxido de carbono e sulfeto de hidrogênio de biogás utilizando soluções absorvedoras - Freddo, Alessandra (2017)
Biogas is a product originated from the anaerobic digestion of organic matter that has, mainly, methane (CH4), carbon dioxide (CO2), hydrogen sulfide (H2S) and steam, among others in smaller quantity. For these gases, it is sought to optimize the process to increase the amount of methane and to reduce those of carbon dioxide and hydrogen sulfide. CO2 gas reduces the combustion power of biogas and H2S is highly corrosive, damaging equipment and piping. Currently, several technologies have been used for the treatment and purification of biogas and among them are those that use the principle of absorption in liquids. The objective of this research was to evaluate the efficiency of CO2 and H2S removal with different absorber solutions and to compare them in a technical feasibility study for specific scenarios. The absorber solutions used were: ultrapure water, ozone gas (O3) solubilised in water, solution with sodium hydroxide (NaOH), solution with calcium hydroxide (Ca(OH)2), solution containing iron complexed with ethylenediaminetetraacetic acid (Fe/EDTA) and a biofertilizer from an anaerobic biodigestor fed with swine biomass. All these tests were performed under room temperature and pressure conditions. For the batch tests with the solutions of ultrapure water, water solubilized ozone gas, NaOH solution (0.5 mol.L-1), Ca(OH)2 solution (0.250 mol.L-1) and Fe/EDTA solution was used a biogas from an agroindustry biodigester. For the biofertilizer trials a synthetic biogas was used. For the determination of optimal treatment conditions with the Fe/EDTA solution, a Rotational Central Compound Design (DCCR) was used in which the Fe/EDTA concentration of the solution and the pH were evaluated. In a second DCCR, the effect of the regeneration of the solution on the saturation time with H2S was evaluated. In the study of biogas treatment with the biofertilizer, a Central Compound Design (DCC) was applied to verify the effect of the concentration of biofertilizer and pH on the saturation time of the solution and efficiency in the removal of CO2 and H2S from the biogas. The results indicated that the solution containing the solubilized ozone gas had no significant effect on the treatment of biogas when compared to ultrapure water. When the alkaline solutions were compared, the solution with NaOH presented a high efficiency in the removal of CO2 (83.98%) and H2S (100%) of the biogas, on average, and the Ca(OH)2 solution indicated lower efficiency in the removal of CO2 (30.1%) with removal of 100% of H2S. The results of the fresh biofertilizer assays indicated a removal efficiency of on average 50% of CO2 and 90% of H2S, and the optimization tests indicated that the pH variation does not change considerably the removal of CO2, with higher removal of H2S at alkaline pH. The study with the Fe/EDTA solutions indicated that the pH has a direct influence on the saturation time of the solution with H2S in regenerated and freshly prepared solutions. This study made it possible to evaluate the performance of these solutions in the treatment of biogas and its technical feasibility, which generates an in depth knowledge that allows to evaluate its applicability in real scale.